A List of Edible Plant Species from 14 databases standardized and harmonized according to GBIF - Fauchon, Paul; Estrada Carmona, Natalia (2025)
The main idea of this project is to gather plant species (and their GBIF ID) from various databases including 1) crop databases : Ecocrop and Crops and their origins (Milla et al. 2020) 2) FAO commodity species database (Khoury et al. 2023), 3) plant species found in School gardens (SG) and home-grown school feeding (HGSF) programs (Estrada-Carmona et al. 2025) and 4) a list of databases of orphan, neglected, underutilized (nutritious) species.